1966
DOI: 10.1063/1.1727649
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Rotation on the Viscosity of Liquids

Abstract: Articles you may be interested inInfluence of temperature and viscosity on anthracene rotational diffusion in organic solvents: Molecular dynamics simulations and fluorescence anisotropy studyThe effect of molecular association and tube dilation on the rotational viscosity and rotational diffusion in nematic liquid crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…This assumption is consistent with the viscosity theories [22,23,24] which will be disc ussed below. The fractional number of molecules which relaxes with relaxation time Ti between In Ti-1f2 dIn T and In Tj+ 1f2 dIn T is (9) where gE(Ei) dE is the fractional number of molecules with activation free energy between Ei -1f2dE and Ei + IhdE.…”
Section: I Lsupporting
confidence: 68%
See 1 more Smart Citation
“…This assumption is consistent with the viscosity theories [22,23,24] which will be disc ussed below. The fractional number of molecules which relaxes with relaxation time Ti between In Ti-1f2 dIn T and In Tj+ 1f2 dIn T is (9) where gE(Ei) dE is the fractional number of molecules with activation free energy between Ei -1f2dE and Ei + IhdE.…”
Section: I Lsupporting
confidence: 68%
“…We have found in Ge02 supporting evidence that the departure from th e Arrhenius c urve for viscosity is caused by the app earance of a distribution of relaxation time s, and , furth er , that the associa ted distribution of activation e nergies has not only higher activation energies but also lowe r. The present theories which predict non-Arrhenius behavior are ty pified by the work of Ree, Ree, and Eyring [22] , Ada m and Gibbs [23], and Davies and Matheson [24]. These theories picture the molecules as being relati vely free at high te mperatures in the Arrhenius region, and / connect the appearance of non-Arrhenius behavior with some increase in cooperation between molecules , ' or a loss in certain degrees of freedom as the temperature is lowered.…”
Section: I Lsupporting
confidence: 49%
“…The physical model treated by Davies and Matheson (41,43) involves restriction of rotational modes of freedom as the amount of free volume is reduced. In the Arrhenius region the molecules have sufficient rotational freedom to reorientate several times between translational jumps.…”
Section: Energies Of Activation For Conductivity At Constant Volume Amentioning
confidence: 99%
“…The slip limit is not unexpected since it has been found to apply to a variety of neat non-associative dense liquids [39], in addition to several other glass forming fluids, such as glycerol [40], O-terphenyl [7] and phenyl-o-cresol [5]. It seems that if rotational motions occurred only as a result of translational jumps below Tk, as proposed [17], stick boundary conditions would be applicable. However, we need to emphasize the approximate nature of our conclusions regarding the validity of the Debye equation because of the possible presence of cooperative motions and of the anisotropic nature of reorientations in the supercooled state.…”
Section: Temperature Effects On Ring Motionsmentioning
confidence: 91%
“…Ubbelholde et al [15] and Rao et al [16] attributed the anomalous behaviour to cluster formation. Davies and Matheson [17] explained the viscosity anomaly in terms of the free volume theory originally proposed by Doolittle [12], Williams, Landel and Ferry [18] and Cohen and Turnbull [11]. They concluded that at temperatures above Tk, the molecules can fully reorient about at most one symmetry axis during the time between translational jumps.…”
Section: Downloaded By [University Of Arizona] At 22:51 05 February 2015mentioning
confidence: 97%